Exploring the relation between income mobility and inequality at the regional level using EU-SILC microdata - Mogila, Zbigniew (2020)
This paper investigates empirically the impact of labour-related income inequality on income mobility in French and Spanish NUTS2 regions. We explore whether the negative relation between income inequality and mobility - known as the Great Gatsby Curve - is also present in the short and medium run. Using longitudinal microdata from the EU-SILC, we construct NUTS2-level measures of relative income mobility from transition matrices between income deciles for 2-year and 4-year income trajectories and measures of income inequality based on the Gini index and inter-decile ratios. We then combine these measures with other regional-level factors and implement regression models to test the relation between income inequality and income mobility. The regional perspective allows us to investigate the extent to which territorial heterogeneity may also affect income mobility. The findings from the regression analyses do not provide evidence of a significant relationship between income mobility and income inequality, at least when considering mobility over the short-to-medium term (i.e. up to 4 years).